Analysis of productions on teaching in the early years present in the proceedings of the 15th National Meeting of Teaching Practice in Geography (ENPEG) - Lopes, Debora Cristina (Revista Ensino de Geografia (Recife), 2025)
This article aims to analyze recent production that deals with teaching Geography in the early years of elementary school. The research, with a qualitative approach and a documentary bibliographic nature, is based on productions published on the teaching of Geography in the initial years, at the 15th National Meeting of Geography Teaching Practice (ENPEG), held in 2022. These works were selected based on the presence, in the title and/or keywords, of the descriptor “initial years”. Of the total of 404 works shared in the Annals, twelve publications on early years were identified, distributed across all Brazilian regions. When reading the publications, three categories of analysis were prioritized: different languages ​​in Geography teaching, curricular issues and teacher training. The results point to the need for initial training that makes it possible to understand the importance of teaching Geography, the understanding of the fundamental concepts of this science, as well as the different methodologies to develop the reading of the world in students in the early years of elementary school.